‘Reckless Eyeballing’: Written and Oral Narratives in Genesis 16.4-5 - Splawn, Jane (Feminist theology, 2013)
This essay considers how current theories of narrative (both written and oral) inform how we read the complexities of the relationship(s) among Abraham, Sarah, and Hagar in Gen. 16.4-5. It argues that, while we may no longer have access to the oral counter narrative of Gen. 16.4-5, deconstructive criticism, which–among other things – teaches us that a text can be most revealing in those places in which it is most notably silent, may allow for a possible recovery of the oral, unrecorded narrative of the servant Hagar.